2014
DOI: 10.1186/1472-6963-14-372
|View full text |Cite
|
Sign up to set email alerts
|

Societal cost-effectiveness analysis of the 21-gene assay in estrogen-receptor–positive, lymph-node–negative early-stage breast cancer in Japan

Abstract: BackgroundBreast-cancer incidence and mortality have been increasing in Japan. Japanese-specific clinical validity and utility data for the 21-gene assay (Oncotype DX® Breast Cancer Assay; Genomic Health, Inc., Redwood City, USA) are now available. The objective of this study was to evaluate the cost-effectiveness of the 21-gene assay for the guidance of adjuvant chemotherapy decisions in estrogen-receptor–positive, lymph-node–negative, early-stage breast cancer patients, from the Japanese societal perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…However, these biomarkers test different sets of breast cancer-related genes (9). Although these diagnostic tests are typically used as prognostic markers in early-stage breast cancer, they are costly and require multiple markers (10). Therefore, simpler and easily measurable biomarkers with highly accurate assays need to be developed for the treatment of patients with breast cancer.…”
Section: Characterization Of Kif20a As a Prognostic Biomarker And Therapeutic Target For Different Subtypes Of Breast Cancermentioning
confidence: 99%
“…However, these biomarkers test different sets of breast cancer-related genes (9). Although these diagnostic tests are typically used as prognostic markers in early-stage breast cancer, they are costly and require multiple markers (10). Therefore, simpler and easily measurable biomarkers with highly accurate assays need to be developed for the treatment of patients with breast cancer.…”
Section: Characterization Of Kif20a As a Prognostic Biomarker And Therapeutic Target For Different Subtypes Of Breast Cancermentioning
confidence: 99%
“…Tumor Size (cm) applied the RS results to recommend and prescribe chemotherapy more judiciously to patients with nodenegative and node-positive breast cancer. 21,22,33,35,41 In this study, we observed a reduction in chemotherapy recommendations after Breast Recurrence Score testing across all groups, indicating that the clinical utility of the test across nodal status endures in Latin America. Furthermore, the post-TAILORx treatment recommendations observed in our study for node-negative breast cancer were generally reflected clinical practice guidelines that advise chemotherapy for patients with RS 26-100 of any age, consideration of chemotherapy for patients with RS 16-25 who are premenopausal, and no chemotherapy for patients with RS 0-25 who are postmenopausal or RS 0-15 who are premenopausal.…”
Section: Discussionmentioning
confidence: 61%
“…16,18 The clinical utility of the Breast Recurrence Score test, or the capacity of the test to change clinical practice and improve outcomes of patients with node-negative or node-positive breast cancer in a costeffective manner, has been demonstrated in numerous studies conducted worldwide. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] One such study conducted in Mexico (N = 96; node-negative and node-positive breast cancer) showed that knowledge of RS results led to a 28% reduction in recommendations for chemotherapy at one center. 24 Another study (N = 551; node-negative and node-positive breast cancer) showed that physicians in Peru made treatment recommendations in line with RS results such that the rate of chemotherapy recommendations increased with RS groups of higher risk (13% with RS 0-17, 77% with RS 18-30, and 98% with RS 31-100).…”
Section: Introductionmentioning
confidence: 99%
“…However, knowing the costs makes it possible to adapt health policies, allocate health budgets, adjust social assistance and evaluate the contribution of innovations. Most published health economics, cost-effectiveness or cost-utility studies have focused on a specific drug [10], surgical procedure [11] or examination [12,13]. Few studies have assessed the overall direct costs of one-year management, including medical and non-medical costs, in order to elucidate the distribution of costs during the various phases of health care (diagnosis, treatment, follow-up), which would be useful for policymakers to inform decisions on health care funding.…”
Section: Introductionmentioning
confidence: 99%